2017
DOI: 10.1038/srep46607
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Tsunami Ionospheric Disturbances with a Stand-Alone GNSS Receiver: A Preliminary Feasibility Demonstration

Abstract: It is well known that tsunamis can produce gravity waves that propagate up to the ionosphere generating disturbed electron densities in the E and F regions. These ionospheric disturbances can be studied in detail using ionospheric total electron content (TEC) measurements collected by continuously operating ground-based receivers from the Global Navigation Satellite Systems (GNSS). Here, we present results using a new approach, named VARION (Variometric Approach for Real-Time Ionosphere Observation), and estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 53 publications
7
94
0
3
Order By: Relevance
“…CTID match the period, velocity, and propagation direction of the tsunamis causing them. Consequently, tracking CTID provides an opportunity to follow the propagation of tsunamis and can potentially be used for near‐real‐time tsunami warning systems (e.g., Najita et al, ; Savastano et al, ).…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
See 2 more Smart Citations
“…CTID match the period, velocity, and propagation direction of the tsunamis causing them. Consequently, tracking CTID provides an opportunity to follow the propagation of tsunamis and can potentially be used for near‐real‐time tsunami warning systems (e.g., Najita et al, ; Savastano et al, ).…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
“…CTID match the period, velocity, and propagation direction of the tsunamis causing them. Consequently, tracking CTID provides an opportunity to follow the propagation of tsunamis and can potentially be used for near-real-time tsunami warning systems (e.g., Najita et al, 1974;Savastano et al, 2017). Hines (1972) and Peltier and Hines (1976) were the first who theoretically predicted that sea surface variations typical of tsunamis can seed internal gravity waves with amplitudes strong enough to generate ionospheric signatures.…”
Section: Tsunamis and Their Signatures In The Atmosphere And Ionospherementioning
confidence: 99%
See 1 more Smart Citation
“…GPS data have proven the potential of early tsunami warning [Blewitt et al, 2007;Sobolev et al, 2007;Singh et al, 2012;Hoechner et al, 2013;Savastano et al, 2017]. In literature, so far, the focus is mainly on the advantages of the GPS data in recovering large earthquake parameters, but recently there is a growing interest in developing automated algorithms for real-time determinations of seismological parameters and deformation analysis for smaller seismic events [Melgar et al, 2015;Crowell et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we call the GW signals of ionospheric disturbances ionospheric GWs. Studies have shown that various origins, including solid earth events, such as earthquakes and tsunamis [6][7][8][9], and tropospheric weather events, such as typhoons, penetrative convections, and jet streams [10][11][12], can trigger GWs and propagate upwards to ionospheric height.…”
Section: Introductionmentioning
confidence: 99%